Activated Carbon for Food Packaging Application: Review - CHAEMSANIT, Siriporn; MATAN, Narumol; MATAN, Nirundorn (Walailak Journal of Science and Technology (WJST), 2017)
Recently, several types of food packaging have been developed which are able to prolong shelf-life of, and maintain the quality and safety of, products. Many kinds of material have been applied to food packaging, in the forms of film, sachets, or pads, to protect, eliminate, or inhibit undesirable changes in food. Based on the increasing concern about environmental sustainability, there have been many attempts to develop a natural biodegradable food packaging. Activated carbon as a multifunctional material is an interesting alternative choice. Apart from its ability to naturally degrade, non-toxicity, and low cost, it possesses remarkable adsorption potential. Its abilities are versatile, and could be used in various application purposes. Thus, its ability strongly depends on its pore structure and surface chemistry. Although it has been known for its effect on hydrophobic substances, the modification of pore size and surface property of activated carbon could improve its affinity to hydrophilic substances. Two means of activated carbon applications in food packaging were classified, according to its adsorption and releasing ability. The first mean is the application of activated carbon for the emission of antimicrobial agents in the vapor phase and nanoparticles inside food packaging. The second mean is the application of activated carbon for scavenging of factors affecting food quality inside packaging, such as water vapor, oxygen, ethylene, and odor. In this paper, the adsorption-releasing mechanism of activated carbon on some of the antimicrobial agents and vapor phase substances are discussed. Additionally, the potential role of activated carbon in food packaging is summarized.